Self-powered wearable electronics. (13th October 2020) - Tan, Puchuan; Zou, Yang; Fan, Yubo; Li, Zhou
Abstract: Wearable electronics are an essential direction for the future development of smart wearables. Among them, the battery life of wearable electronics is a key technology that limits their development. The proposal of self-powered wearable electronics (SWE) provides a promising solution to the problem of long-term stable working of wearable electronics. This review has made a comprehensive summary and analysis of recent advances on SWE from the perspectives of energy, materials, and ergonomics methods. At the same time, some representative research work was introduced in detail. SWE can be divided into energy type SWE and sensor type SWE according to their working types. Both types of SWE are broadly applied in human–machine interaction, motion information monitoring, diagnostics, and therapy systems. Finally, this article summarizes the existing bottlenecks of SWE, and predicts the future development direction of SWE.